The Effect of Giving Ginger Warm Compresses to The Headache Scale In Hypertensive Patients at Grandmed Hospital, Lubuk Pakam - Sari Desi Esta Ulina Sitepu; Pratiwi Christa Simarmata; Selamat Tuahta Sipayung (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
One of the sign and symptoms of hypertension is headache. Headache occur due to atherosclerosis which causes spasm of the blood vessels (arteries) and decreased oxygen in the brain. The pain can be treated with non pharmacological management, one of which is a warm gingger compress (zingiber officinale). The purpose of this research activity was to measure the effect of giving warm ginger compresses on reducing the headache scale in hypertensive patients at Grandmed Lubuk Pakam Hospital. The type of research used in this study is a quasi experimental approach with a one group pretest-posttest design approach, with a purposive sampling technique. Giving warm ginger compresses to 37 patients suffering from hypertension at Grandmed Lubuk Pakam Hospital. Data collection was carried out using observation sheets and providing an intervention with warm ginger compresses in hypertensive patients. Observations of headaches in hypertensive patients carried out twice, namely before being given a warm ginger compress and after being given a ginger warm compress then the results were recorded on the observation sheet. Teh results of statistical tests using the paired test showed the value of p=0,000, p<? (0,000<0,05). The results obtained showed that there was a decrease in the level of headache in hypertensive patients before and after being given warm ginger compresses. It is expected that nurses can minimize the use of analgesic drugs to reduce headaches and use warm compresses for non pharmacological management.